1991
DOI: 10.1017/s0950268800048949
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and genetic homogeneity ofStreptococcus uberisstrains from the bovine udder

Abstract: SUMMARYDNA-fingerprints (Hind III) of Streptococcus uberis field isolates from New York State and Europe showed substantial homogeneity, but were different to those of the type strain of the newly proposed psychrophilic species S. parauberis. S. uberis strains had major SDS-heat extracted antigens of molecular masses (Mr) < 14, 40-41, 42-43, 59-61, 80-86 and 118-122 kDa following immunoblotting with rabbit hyperimmune sera. Bovine sera and milk reacted with the 40-41 and 118-122 kDa antigens. Variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…DNA-fingerprinting of Strep. uberis was first described around 1990 [ 71 , 83 , 208 ]. One early study suggested substantial strain homogeneity among Strep.…”
Section: Streptococcus Uberismentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-fingerprinting of Strep. uberis was first described around 1990 [ 71 , 83 , 208 ]. One early study suggested substantial strain homogeneity among Strep.…”
Section: Streptococcus Uberismentioning
confidence: 99%
“…One early study suggested substantial strain homogeneity among Strep. uberis isolates [ 71 ], which may have been due to the fact that molecular typing methods were in their infancy and lacked discriminatory power. Since then, almost every study has shown a considerable level of heterogeneity among strains within and between herds, whether based on RAPD-typing [ 67 , 90 , 217 ], rep-PCR [ 207 ], PFGE [ 11 , 46 , 145 , 203 ], or MLST [ 151 , 193 ].…”
Section: Streptococcus Uberismentioning
confidence: 99%
“…As mentioned in previous work [ 6 ], Western blotting assays using a polyclonal anti-GB streptococci antibody evidenced two stained immunogenic proteins in Streptococcus uberis cell wall proteins’ pattern besides the expected immunogenic protein set of Streptococcus agalactiae . According to Groschup and colleagues [ 7 ], some Streptococcus uberis strains can also react with Lancefield group B serum.…”
Section: Introductionmentioning
confidence: 99%